The Problematika Pendampingan Orang Tua pada Anak dalam Proses Belajar di Rumah Masa Pandemi Covid-19 - Faqih Abdul Bashir; Bramastia; Eka Khristiyanta Purnama (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
The role of parents in assisting children to study at home has strengthened again during the Covid-19 pandemic. However, parents experience various obstacles in assisting their children's learning process. The study aimed to discover parents' obstacles when assisting children in learning from home. The data collection method used a survey of students throughout Indonesia. The cluster random sampling technique obtained as many as 46,547 parents online and 602 through Short Message Service (SMS). A sampling of respondents in each province, Frontier, Remote and Disadvantaged (3T region) and non-3T regions. The data analysis in this study used a quantitative descriptive method. The results showed that 42 % of parents had difficulty understanding the learning material, 32% of parents lacked focus in assisting children, 35 % of parents could not interact directly with teachers, 15 % of parents did not have digital devices, 30 % of parents did not have the skills to use digital devices, 30 % of parents constrained by an inadequate internet network, in addition there are 3 % of parents who experience problems with an inadequate electricity network. This study concludes that the problem of parents' assistance to children in the learning process at home during the COVID-19 pandemic is the lack of understanding of children's learning material, lack of access to interaction with teachers, lack of facilities and infrastructure, and lack of ability to master technology.